Epilogue: degrees of transparency (Linguistics in Amsterdam, 2011)
In this epilogue the results of the analyses of four different languages in the preceding papers are compared. It is shown that the degrees of transparency of these languages can be represented on an implicational scale, and that the features themselves can be ranked on a transparency scale as well. It is furthermore shown that Esperanto occupies a somewhat different position within the sample as it was designed as a phonologically and morphologically transparent language, but lacks transparency in its syntax.